Pemberdayaan Kesehatan dan Ekonomi Keluarga melalui Edukasi Kesehatan, Manajemen Usaha, dan Pencatatan Keuangan bagi Pelaku UMKM - Juli Evianna Purba; Rudyanto Simanjuntak; Alice Paulina Purba; Edy Terdjo (Jurnal Pemberdayaan Masyarakat, 2025)
This community service activity aims to empower Micro, Small, and Medium Enterprises (MSMEs) through a multidisciplinary approach, including health education, business management training, and basic financial recording. The main issues faced by MSME actors include low awareness of occupational health, weak business planning and management, and a lack of understanding in financial transaction recording. The activity was carried out in Sukamaju Sub-district, Cempaka Putih District, Central Jakarta, involving 30 participants from various micro-enterprises. The implementation methods included interactive lectures, practical simulations, group discussions, and evaluations through pre-tests and post-tests. The results showed a significant improvement in participants’ understanding of occupational health, their ability to develop business strategies, and independently record financial transactions. The integrative approach involving nursing, management, and accounting has proven effective in improving the quality of life and economic resilience of MSME families. This activity highlights the importance of cross-disciplinary collaboration in supporting sustainable community empowerment and promoting economic self-reliance at the grassroots level.